PELATIHAN SPEAKING BAHASA INGGRIS DENGAN MENGGUNAKAN PLATFORM ZOOM MEETING PADA STAFF BIRO KEUANGAN BP BATAM - Suswanto Iswandi Megah; Eka Wilany; Desi Surlitasari Dewi (ASOSIASI IDEBAHASA KEPRI, 2022)
English is very important for communication between countries so that BP batam is a government agency that cannot be separated from developing its English language skills. LPPM Unrika's collaboration with BP Batam Finance Bureau staff in implementing online English language training during the pandemic to improve English language skills. Overall service activities are carried out in a span of 6 months (July-August 2021). The post-test results obtained a conclusion that the basic English skills of the inmates were very good with an average score of 81.8, while the lowest score was 80 and the highest score was 85. When compared to the pre-test where the lowest score was 71.6 and the highest was 80, with an average of 77.1. So the average result of the pre-test and post-test scores is 79.4, so the achievement value of BP Batam's financial bureau staff increases significantly.